Trade Cards in 18th-Century Consumer Culture: Circulation, and Exchange in Commercial and Collecting Spaces - Hubbard, Phillippa (Material Culture Review, 2012)
This paper examines the movement of trade cards in 18th-century consumer and collecting cultures. These unique graphic advertisements supported socio-economic relationships for a limited period in the history of consumption and became sought-after graphic commodities. I consider the ways in which trade cards traversed public commercial centres and private domestic spaces as mobile advertisements, personalized bills, and miniature artworks accruing new meanings and uses as they passed through space and time. The paper complicates the traditional categorization of trade cards as “ephemera.” It suggests that trade cards, rather than functioning as throwaway fragments of promotional culture, circulated within commercial society and collecting circles as valued tokens of private economic exchanges and rarefied objects.